Increase in Vertebral Body Height after Vertebroplasty - Hiwatashi, Akio (AJNR Am J Neuroradiol, 2003)
BACKGROUND AND PURPOSE: During clinical work, we have seen increases in vertebral body height associated with vertebroplasty, but our literature search revealed no reports as to how often and to what degree those increases occur. The purpose of this study was to document the frequency and degree of changes in vertebral body height after vertebroplasty. METHODS: The heights of 85 vertebral bodies in 37 patients were measured before and after vertebroplasty. In addition, one adjacent vertebral body was measured in each patient as a control. Twenty-six patients had compression fractures in the thoracic spine, and 24 patients had compression fractures in the lumbar spine. Vertebroplasty was performed with a bilateral transpedicular approach by injecting polymethylmethacrylate, under biplane fluoroscopic control. Measurements were performed on preoperative MR images and on postoperative CT sagittal reformations. Anterior, central, and posterior vertebral body height measurements were obtained in the midsagittal plane. RESULTS: The average increase in vertebral body height was 2.5 mm anteriorly, 2.7 mm centrally, and 1.4 mm posteriorly. Thirteen of 85 treated vertebrae remained unchanged. All control vertebral bodies also remained unchanged. CONCLUSION: Vertebral body height often increases during vertebroplasty. The clinical significance of increasing vertebral body height is unknown.